The Role of Ubiquitin-Like Interferon (IFN)-Stimulated 15 and IFN Gamma Genes Polymorphism with the Severity and Serum Biochemical Markers in COVID-19 Patients - Khadijah Gatfan Hosseien; Parisa Tahmasebi; Hayder Obayes Hashim; Alaa Tareq Shakir; Zahra Bozorgi Moghadam (Medical Journal of Babylon)
Background: The ubiquitin-like interferon-stimulated 15 (ISG15) gene belongs to the group of “interferon-stimulated genes (ISGs).” These ISGs are powerful and rapid type 1 interferon (IFN)-stimulated response proteins that suppress viral replication. IFN-gamma (IFN-γ) is a kind of cytokine that plays a significant role in both the induction and regulation of a wide variety of immune responses. Objectives: This study examined the relationships between rs1921 and rs1861494 single nucleotide polymorphisms with the manifestation of coronavirus disease 2019 (COVID-19) symptoms in patients and the status of biochemical markers in previously diagnosed cases. Materials and Methods: A total of 100 blood samples were collected from COVID-19 patients in different cities in Iraq and tested for hematological parameters, including complete blood count, as well as biochemical markers, such as D-dimer, ferritin, and C-reactive protein (CRP). Additionally, the polymerase chain reaction-restriction fragment length polymorphism technique was used to analyze the genotyping of rs1921 and rs1861494 polymorphisms. Results: The results show that different rs1921 genotypes have significant associations with hemoglobin levels, white blood cell counts, basophil counts, and loss of smell. In contrast, there were no significant differences in red blood cell counts, monocyte counts, lymphocyte counts, platelet counts, CRP levels, D-dimer levels, ferritin levels, fever duration, or taste loss. Furthermore, rs1861494 genotypes revealed no significant differences in any of the patients’ parameters. Conclusion: Our results indicate that rs1921 is more correlated with COVID-19 patients’ parameters than rs1861494, suggesting the need for further investigation to enhance understanding.